Conical shell illumination incorporating a moving aperture for depth-resolved high-energy X-ray diffraction. Issue 5 (2nd February 2023) - Spence, Daniel; Dicken, Anthony; Downes, David; Rogers, Keith; Evans, Paul
Abstract : To retrieve crystallographic information from overlapping sample volumes requires a high-energy probe using a point detector. Abstract : In many applications, the main limitation of X-ray absorption methods is that the signals measured are a function of the attenuation coefficient, which tells us almost nothing about the chemical or crystallographic nature of objects under inspection. To calculate fundamental crystallographic parameters requires the measurement of diffracted photons from a sample. Standard laboratory diffraction methods have been refined for well over a century and provide 'gold standard' structural models for well-prepared samples and single crystals but have little applicability for thick heterogeneous samples as demanded by many screening applications. We present a new high-energy X-ray diffraction probe, which in comparison with previous depth-resolving hollow beam techniques, requires a single beam, point detector and a simple swept aperture to resolve sample signatures at unknown locations within an inspection space. We perform Monte Carlo simulations to support experiments on both single- and multiple-material localisation and identification. The new probe is configured and tested using low-cost commercial components to provide a rapid and cost-effective solution for applications including explosives detection, process control and diagnostics.